Relationship Breakup: Analysis of Motives and Hypoactive Sexual Desire in Young Adults in Southeastern Mexico - Estrada Carmona, Sinuhé (2025)
The breakup of a romantic relationship can have a significant impact on the individual, but little has been discussed about its effect on hypoactive sexual desire, which is associated with a decrease in sexual desire, making relationships difficult due to low motivation for sexual activity (Cabello-Santamaría & Palacios, 2012). The decline in sexual interest is more frequently observed in women, and breakups are often experienced as traumaticevents (Hartman, 2017). Thus, the present study aims to analyze the relationship between the reasons for romantic breakups and hypoactive sexual desire in women. This is a mixed-method study involving 41 women aged 20 to 35 who had been in a romantic relationship lasting between 1 and 12 months. The Inhibited Sexual Desire Test byMasters et al. (1994) and the Inhibited Sexual Desire Assessment (DSI) by J.Mª. Farré and Mª.G. Lasheras (2002) were used. According to the results, the most common reasons for breakups that lead to experiencing hypoactive sexual desire and inhibited sexual desire were infidelity, boredom, arguments, distance, violence, disagreements, and lack of communication factors that vary according to individual, social, and cultural contexts.